Behavior of Hybrid Reactive Powder Concrete Columns Exposed to Chloride Attack - Salman, Mohammed \m.; Jarallah, Husain K.; Al-Behadili, Raed Satar (Al-Nahrain Journal for Engineering Sciences, 2018)
In this paper, the cross section behavior of reinforced concrete columns made of normal and hybrid reactive powder concrete (hybrid by steel and polypropylene fibers) under concentric and eccentric vertical load was study. The casted columns were cured in two different type tap water for 28 days and chloride water for six months. Chloride salts with concentration was 8341.6 mg/l. Three variables were adopted in the experimental program; concrete type, curing type and the eccentricity of vertical load. Twenty (120x120x1200) mm columns were casted and tested depending on these variables. The different eccentricities were (0, 50,100 and 150) mm and where (e/h) were (0, 0.42, 0.83 and 1.25) respectively from the center of column, the other types of loading are tested the specimens as beam._x000D_The experimental results showed increasing in ultimate load capacity and higher chlorides resisting for hybrid reactive powder concrete in comparison with normal concrete in both types of curing (tap and chloride water). Through studying load deflection, test results for Normal Strength Concrete (NSC) and Hybrid Fiber Reactive Powder Concrete (HFRPC) columns that deflection for columns cured in chloride water more than tap water when compared at the same load that also by increase eccentricity leads to an increase in deflection for both cured and The neutral axis depth for HFRPC columns is more than NSC at the same load also when eccentricity increases, the compression zone decreases and neutral axis also decrease by increase eccentricity. These results occur when columns are cured in tap and chloride water._x000D_